2020
DOI: 10.1177/2382120520951821
|View full text |Cite
|
Sign up to set email alerts
|

From Creation to Evaluation: A Comprehensive Global Health Scholars Program for Graduate Medical Education Trainees

Abstract: Introduction: Recently, participation in clinical global health rotations has significantly increased among graduate medical education (GME) trainees. Despite the many benefits these experiences provide, many ethical challenges exist. Well-intentioned partnerships and participants often encounter personal and professional dilemmas related to safety, social responsibility, and accountability. We designed a curriculum to provide trainees of all specialties with a comprehensive educational program aimed at delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Participation in a scholarly project is also required including any of the following: poster or abstract, opinion or clinical reflection piece, peer-reviewed publication, educational material development for trainees or healthcare workers, or quality improvement initiatives. 28 In sum, these educational components and practicum will help address the Global Health Core competencies as developed by the Joint US/Canadian Committee on Global Health Core Competencies, which include the six areas of (1) Global Burden of Disease, (2) Health Implications of Migration, Travel, and Displacement, (3) Social and Environmental Determinants of Health, (4) Globalization of Health and Healthcare, (5) Healthcare in Low-Resource Settings, and (6) Health as a Human Right and Development Resource. 29 Similar resources can be found online for institutions that do not have global health education programs for residents.…”
Section: Rotation Creation Predeparture Requirementsmentioning
confidence: 99%
“…Participation in a scholarly project is also required including any of the following: poster or abstract, opinion or clinical reflection piece, peer-reviewed publication, educational material development for trainees or healthcare workers, or quality improvement initiatives. 28 In sum, these educational components and practicum will help address the Global Health Core competencies as developed by the Joint US/Canadian Committee on Global Health Core Competencies, which include the six areas of (1) Global Burden of Disease, (2) Health Implications of Migration, Travel, and Displacement, (3) Social and Environmental Determinants of Health, (4) Globalization of Health and Healthcare, (5) Healthcare in Low-Resource Settings, and (6) Health as a Human Right and Development Resource. 29 Similar resources can be found online for institutions that do not have global health education programs for residents.…”
Section: Rotation Creation Predeparture Requirementsmentioning
confidence: 99%
“…One study of a global health program report from 84 medical trainees in various specialties, revealed that 95% would recommend the program, 84% felt more prepared to deliver global health care, and 78% reported career plans that included global health. This study concluded that such a health education program across specialties could be feasible and effective [ 2 ]. However, a group of medical trainees are not directly comparable with a group of international PhD students.…”
Section: Introductionmentioning
confidence: 99%